Acute desipramine restores presynaptic cortical defects in murine experimental autoimmune encephalomyelitis by suppressing central CCL5 overproduction. (May 2014) - Di Prisco, Silvia; Merega, Elisa; Lanfranco, Massimiliano; Casazza, Simona; Uccelli, Antonio; Pittaluga, Anna
<x xml:space="preserve">Abstract</x> Background and Purpose Altered glutamate exocytosis and cAMP production in cortical terminals of experimental autoimmune encephalomyelitis (EAE) mice occur at the early stage of disease (13 days post‐immunization, d.p.i.). Neuronal defects were paralleled by overexpression of the central chemokine CCL5 (also known as RANTES), suggesting it has a role in presynaptic impairments. We propose that drugs able to restore CCL5 content to physiological levels could also restore presynaptic defects. Because of its efficacy in controlling CCL5 overexpression, desipramine (DMI) appeared to be a suitable candidate to test our hypothesis. Experimental Approach Control and EAE mice at 13 d.p.i. were acutely or chronically administered DMI and monitored for behaviour and clinical scores. Noradrenaline and glutamate release, cAMP, CCL5 and TNF‐α production were quantified in cortical synaptosomes and homogenates. Peripheral cytokine production was also determined. Key Results Noradrenaline exocytosis and α2‐adrenoeceptor‐mediated activity were unmodified in EAE mice at 13 d.p.i. when compared with control. Acute, but not chronic, DMI reduced CCL5 levels in cortical homogenates of EAE mice at 13 d.p.i., but did not affect peripheral IL‐17 and TNF‐α contents or CCL5 plasma levels. Acute DMI caused a long‐lasting restoration of glutamate exocytosis, restored endogenous cAMP production and impeded the shift from inhibition to facilitation of the CCL5‐mediated control of glutamate exocytosis. Finally, DMI ameliorated anxiety‐related behaviour but not motor activity or severity of clinical signs. Conclusions We propose DMI as an add‐on therapy to normalize neuropsychiatric symptoms in multiple sclerosis patients at the early stage of the disease.